Implementation of a Global Health Equity fellowship established in partnership between an academic institution and governmental agency. Issue 2 (7th November 2022) - Karwa, Rakhi; Schellhase, Ellen; Malati, Christine Y.; Pastakia, Sonak D.; Manji, Imran; Samuel, Jeffrey M.; Miller, Monica L.
Abstract: Health disparities exist globally in high‐income and low‐ and middle‐income countries. They are driven by social determinants of health (SDOH). While a role for pharmacists in addressing SDOH exists, a lack of structured postgraduate training limits pharmacists from being equipped to build innovative programs and contribute to health policy on SDOH in an impactful way. Postgraduate training, specifically, fellowships provides opportunities for pharmacists to develop the needed skills for working with SDOH. The Purdue University College of Pharmacy (PUCOP)‐United States Agency for International Development (USAID) Global Health Equity Fellowship was developed to meet this training need. This 2‐y fellowship represents a partnership between USAID and PUCOP. During the fellowship, time is split between USAID in Washington DC, PUCOP in Indianapolis, Indiana, and the Purdue Kenya Partnership (PKP) in Eldoret, Kenya. The fellowship was developed with a foundation of core values, the creation of a logic model, strategic partnerships, maintaining an adaptable structure, and intentional partner communication. Fellow outcomes were evaluated in three categories: engagement, education, and scholarship. Fellows completed 10 experiential opportunities between three sites and participated in the development of new and supported ongoing care programs and policy implementation in both local and international settings. Fellows completed the following educational outcomes: completed an online Master of Public Health (MPH) through Purdue Global, provided 13 educational presentations and lectures at various sites, and precepted a total of 12 PUCOP advanced pharmacy practice experience (APPE) students and 16 Kenyan pharmacy interns and Master of Pharmacy (MPharm) students. Fellows completed three publications and two abstracts at international conferences. This established training model provides pharmacists with a structured path to gain the knowledge, skills, and attitudes to be leaders in addressing Global Health Equity.